Curasi Rafael, Nancy - (:unkn) unknown (My University, 2026)
Agroindustrial Engineer from the National University of the Altiplano, Environmental Engineer from the Peruvian Union University. Bachelor of Education Sciences from the National University of Education; with more than 19 years of experience. member of the College of Engineers of Peru. Masters studies in Food Science and Technology and Masters in Environmental Engineering from the National University of the Altiplano; carries out research work published in scientific journals and exhibited at National and International congresses. Work area: specialist in Food Technology I and II, physical, chemical and physical-chemical characterization of food. Cereal industry, baking industry; Applied Ecology, Environmental Sanitation, Social Media Management, Air, Soil and Water Pollution; Environmental education and sustainable development. Associate Professor and Assigned to the School of Environmental Engineering.